Perbandingan Kadar Hemoglobin pada Ibu Hamil Sebelum dan Setelah diberi Tablet Fe dengan Vitamin C di Puskesmas Wuryantoro, Wonogiri - Murniatun; Enny Listiawati (LPPM Universitas Abdurrab, 2025)
The incidence of anemia among pregnant women in Puskesmas Wuryantoro in 2022 was 31 cases or 13.08%, then in 2023 there were still 22 cases of anemic pregnant women or 9.65%, where the coverage target for anemic pregnant women should be less than 6.60%. Fe tablets given to pregnant women aim to build iron reserves and red blood cell synthesis. Vitamin C as a combination of Fe tablets can increase the bioavailability of iron, so that iron can maximally increase the hemoglobin content in the body. This study focuses on the effect of the use of iron tablets supported by the administration of Vitamin C to increase the amount of hemoglobin in pregnant women who visit the Wuryantoro Health Center. This research is analytic comparative through pre-experimental one-group pretest-posttest design method. The subjects studied were 25 pregnant women who had never received iron tablets combined with Vitamin C at the Wuryantoro Health Center in February 2025 taken by purposive sampling. The research time was February to March 2025. Examination of hemoglobin levels using Hematology Analyzer. Data analysis with paired sample t-test (related) at a confidence level of 95% data processing with the Statistical Product and Service Solutions (SPSS) program version 27. The research analysis gave a significance value (p) of 0.000 <0.05. The conclusion of this study is that there is a significant difference in hemoglobin levels of pregnant women before and after being given Fe tablets with Vitamin C at the Wuryantoro Health Center, Wonogiri.